Bacterial communities exhibit apparent phosphate concentration-related patterns of community composition, alpha diversity, and phylogenetic structure in the subtropical Daya Bay - Chen, Ye; Ma, Guibin; Wu, Chuangfeng; Peng, Yuyang; Song, Xingyu; Wu, Qinglong L.; Han, Bo-Ping; Ren, Lijuan (Frontiers in Marine Science, 2023)
Increasing anthropogenic activities have caused serious environmental problems and undesirable ecological impacts on bay ecosystems. However, much remains to be learned regarding marine bacterial community assembly and its underlying mechanisms under intensive anthropogenic activities in subtropical bays. In this study, we used the community assembly theory to analyze bacterial community distributions in the subtropical Daya Bay, where the habitats are subject to serious thermal discharge and excessive nutrient load. We found the community assembly of bacterial in the Daya Bay was dominantly shaped by environmental factor of seawater phosphate, followed by temperature, and silicate. High phosphate concentration significantly increased the relative abundance of Actinobacteria, Cyanobacteria, Planctomycetes, and Gammaprotecteria, but reduced the relative abundance of Bacteroidetes and Alphaproteobacteria. Moreover, higher phosphate concentration was found significantly and positively correlated with higher bacterial alpha diversity. Compared with stochastic processes, we found higher phosphate concentration imposed stronger deterministic processes (primarily homogeneous selection) in structuring bacterial community assembly in the subtropical Daya bay, and bacterial communities tended to be higher phylogenetically clustered in higher phosphate-concentration habitats. In summary, we proposed that phosphate is a major environmental determinant in the subtropical Daya Bay and influenced the relative importance of deterministic and stochastic processes in bacterial community assembly.